Existentialism in Extracurricular Poetry Creation: A Hermeneutic Analysis - Sholihah, Husniatin; Simanjuntak, Nensy Megawati (Journal of Language and Literature Studies, 2024)
Poetry is a literary form that conveys the poet's emotions and thoughts through an imaginative and structured process. It is rich in emotion and distinct in its expression. Writing poetry involves channeling imagination into lines and stanzas, reflecting the poet's creative freedom and ownership. Within the framework of existentialism, poets exercise complete freedom in crafting their poetry without external influence. This study employs a qualitative approach using Hermeneutic analysis and data validation techniques, where data are validated through thorough reading to ascertain the meaning of each word and phrase. The data sources consist of seven poetry texts created by members of the extracurricular poetry group at MTs Miftahul Huda Palang Tuban. Data were collected in the form of words, phrases, and stanzas that depict existentialism, particularly individual freedom. The findings reveal five existential themes in the poetry: "me" (29%), "heart" (14%), "love" (14%), "friends" (29%), and "God" (14%). The terms "me" and "best friend" are the most prevalent, highlighting the themes of self-identity and interpersonal relationships as forms of existence. This study demonstrates that the poet's existence is manifested through the choice of words, with the dominant themes reflecting the poet's exploration of identity, relationships, and individual freedom.